Selective breeding to improve resistance against summer mortality in the Pacific oyster Crassostrea gigas : results after 3 generations - Boudry, Pierre; Degremont, Lionel; Bedier, Edouard; Samain, Jean-francois (International triennial Meeting "Aquaculture 2004", 2004)
Summer mortality of adults and juveniles has been reported in the Pacific oyster, Crassostrea gigas, for many years and in several countries. The French multidisciplinary program "Morest" aims to investigate the causes of the summer mortality in Crassostrea gigas. Within this program, we designed multi-site field experiments to assess to what extent genetic variability exists for summer mortality in French populations of C. gigas and to determine whether selective breeding could improve survival.